Forensics of Software Copyright Infringement Crimes: The Modern POSAR Test Juxtaposed With the Dated AFC Test - Vinod Polpaya Bhattathiripad (Journal of Digital Forensics, Security and Law, 2014)
This paper presents a new development in the forensics of software copyright through a juxtaposed comparison between the proven AFC test and the recent POSAR test, the two forensic procedures for establishing software copyright infringement cases. First, the paper separately overviews the 3-stage, linear sequential AFC test and then the 5-phase, cyclic POSAR test (as AFC’s logical extension). The paper then compares the processes involved in each of the 5 phases of the POSAR test with the processes involved in the 3 stages in the AFC test, for the benefit of forensic practitioners and researchers. Finally, the paper discusses some common areas where both the tests will need careful handling while implementing them in the judiciaries across the world.